Home-range and movements of Myrmeciza exsul (aves: thamnophilidae) in two fragmented landscapes in Costa Rica: evaluating functional connectivity - Losada Prado, S. (2012)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2012